2007
DOI: 10.1089/thy.2007.0003
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Gestational Hyperthyroidism and Postpartum Thyroiditis in Treated Patients with Graves' Disease

Abstract: Graves' disease (GD) is one of the most common thyroid diseases that cause hyperthyroidism. Gestational transient thyrotoxicosis (GTT) is nonautoimmune hyperthyroidism that occurs in women with a normal pregnancy. Postpartum transient thyroiditis (PTT) is a destructive thyroiditis induced by autoimmune mechanism in the postpartum period. Hyperthyroidism due to GD usually tends to improve during the course of gestation and exacerbate after delivery. When the patient with treated GD presents with thyrotoxicosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…Tagami et al evaluated the serum hCG values and FT 3 /FT 4 ratios of pregnant GD patients and found that the hCG values were higher and FT 3 /FT 4 ratios were lower in the GTT group than in the non-GTT group [9]. Our results in the present study were consistent with the findings in that report.…”
Section: Disclosure Statementsupporting
confidence: 92%
“…Tagami et al evaluated the serum hCG values and FT 3 /FT 4 ratios of pregnant GD patients and found that the hCG values were higher and FT 3 /FT 4 ratios were lower in the GTT group than in the non-GTT group [9]. Our results in the present study were consistent with the findings in that report.…”
Section: Disclosure Statementsupporting
confidence: 92%
“…17,18 Consequently, a history of autoimmune thyroid disorder particularly Hashimoto thyroiditis, Graves' disease or previous PPT is a predisposing factor leading to a higher risk of developing PPTD (56.1-68%; 44% and 70% respectively). [19][20][21][22] In accordance with this data, we also found an increased incidence of PPTD among women with AITD antedating pregnancy.…”
Section: Resultssupporting
confidence: 86%
“…Women with other autoimmune disorders have an increased risk of PPT. Specifically, the prevalence of PPT is 25% with Type 1 diabetes mellitus (276,277), 25% with chronic viral hepatitis (278), 14% with systemic lupus erythematosus (279), and 44% with a prior history of Graves' disease (280). Individuals who had PPT in a prior episode and who returned to the euthyroid state have a 70% chance of developing PPT in a subsequent pregnancy (281).…”
Section: Question 73: What Is the Prevalence Of Ppt?mentioning
confidence: 99%